2008
DOI: 10.1007/s11999-008-0438-6
|View full text |Cite
|
Sign up to set email alerts
|

Fractures of the Middle Third of the Tibia Treated with a Functional Brace

Abstract: Level II, therapeutic study. See the Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…It was previously thought that sagittal plane proximal tibial deformity was well tolerated because it was in the plane of adjacent joint motion. 27 This concept has since been challenged because knee recurvatum is linked to pathologic intra-articular mechanics and ligamentous injuries. 28 Published literature on indications for surgical treatment is limited.…”
Section: Indications For Treatmentmentioning
confidence: 99%
“…It was previously thought that sagittal plane proximal tibial deformity was well tolerated because it was in the plane of adjacent joint motion. 27 This concept has since been challenged because knee recurvatum is linked to pathologic intra-articular mechanics and ligamentous injuries. 28 Published literature on indications for surgical treatment is limited.…”
Section: Indications For Treatmentmentioning
confidence: 99%
“…55 Despite this shift, closed treatment remains a potentially viable option. 56,57 Patients are typically placed in above knee long leg casts and switched to functional braces after three to five weeks. 58 In Sarmiento's 1989 series of 780 tibial fractures, the nonunion rate was 2.5%, shortening of < 10mm occurred in 90% of patients, and an acceptable angular deformity of < 10 degrees was generally attained.…”
Section: Humeral Diaphysis Fracturesmentioning
confidence: 99%
“…63 2019 systematic review and meta-analysis found that conservative treatment of ankle fractures led to a lower rate of infection, decreased need for further surgery, and improved cost-effectiveness. 57 Despite these findings, closed reduction often failed, and a large percentage of patients were transitioned to the operative group. The rates of malunion (15%) and nonunion (10%) were also higher in the nonoperative group.…”
Section: Ankle Fracturesmentioning
confidence: 99%
“…Although less commonly practiced, closed treatment is a potentially viable option, and typically involves reduction and casting followed transition to functional bracing 5 , 6 , 7 , 8 . The largest case series to date of closed treatment of tibial fractures is by Sarmiento 5 , 6 , 7 , 8 , and shows that in the right practice environment, non-operative treatment can achieve excellent radiographic results in some patients. However, these results were obtained at a specialty clinic in a relatively unique organization, and the generalizability and reproducibility of that system to other orthopaedic surgeons is not well-established 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%